Variações na temperatura, valor nutricional e qualidade sanitária do feno de capim Vaquero (Cynodon Dactylon) e Tifton 85 (Cynodon Spp.) sob diferentes tempos e sistemas de armazenamento - Schmoeller, Marilda (2016)
With the aim to evaluate different storage systems for hay, it held two experiments, which are with Vaquero grass hay and Tifton 85. The first aimed to evaluate the variations in temperature, sanitary quality, occurrence of fungi and mycotoxins in grass hay Vaquero and Tifton 85 under different systems and storage times. The bales with average weight of 6 kg were stored in three environments: in covered shed without side walls covered with transparent canvas, (transparent) in an open environment with double-sided coated canvas (double-sided) and airy closed building (shed). The variables were: temperature (°C) hay; quantification and identification of fungi and yeasts; concentration of mycotoxins Aflatoxin, Zearalenon and Deoxynivalenol. The temperature of hay both the surface and inside the bale has been strongly correlated with ambient temperature. The Penicillium occurred more frequently in the grass hay Vaquero stored on double-sided system (6.13 log CFU g-1). As mycotoxins, transparent canvas the shed systems have a higher occurrence of aflatoxin and deoxynivalenol. Organic matter Vaquero grass collected in the field is more occurrence of Fusarium fungus (4.66 log CFU g-1) and mycotoxin zearalenone (594.2 ug kg-1). The ambient temperature influences the temperature of grass hay bales Tifton 85 and Vaquero. There was occurrence of fungi and mycotoxins in all storage systems adopted, including the organic matter and baling forage. The second study was to evaluate the nutritional value of grass hay Tifton 85 and Vaquero under different storage times and conditions. The experimental design was completely randomized in split plot scheme in time with 18 treatments, five replicates and a burden for experimental unit. The treatments were a combination of two types of grass (Vaquero and Tifton 85) with three types of storage system (shed, transparent canvas and double-sided), allocated in installments, and three storage times (30, 60 and 90 days), which constituted the sub parcels. Additional treatments were incorporated into the analysis, being represented by baling both grasses (time zero), which also had five replications, totaling 20 treatments and 100 experimental units. The variables expressed as% of dry matter, were: dry matter (DM), mineral matter (MM), neutral detergent fiber (NDF), insoluble protein in neutral detergent (PIDN), acid detergent fiber (ADF) protein acid detergent insoluble (PIDA), lignin (LIG), cellulose (CEL), hemicellulose (hemic), crude protein (CP) and in vitro digestibility of dry matter (DM). It is observed that the production of DM was greater (87.6%) at 90 days storage system transparent bag. For MM, there is a higher average (9.46%) at 90 days double-sided system. The Vaquero grass PB was higher (14.3%) when compared to the Tifton 85 (11.8%). IVDMD has obtained average (71.6%) at 30 days of storage for the double-sided system. It is found smaller PID values for both grasses double system compared with 60 days of storage. The Vaquero grass in the shed system had the lowest value PIDA to 90 days of storage. For pulp the biggest averages observed are double-sided systems at 90 days for to grass Tifton 85 and Vaquero. The lowest ADF content was found in system transparent for the grass bag Vaquero 60 days. The lowest average observed for the lignin levels it was (2.81%) in transparent canvas system 90 days. The highest levels were observed in FDN double-sided system 90 days of storage (71.4%). Hemicellulose to the highest content was found with a time of 90 days the shed system. Grasses Tifton 85 and Vaquero had no change DM contents for a period of 90 days of storage in the studied systems. The Vaquero and Tifton 85 grasses have similar nutritional value during storage. The storage system with double face canvas promotes decrease of the nutritional value of forage studied between 60 and 90 days of storage. Both the Tifton 85 grass as the Vaquero can be stored for a period of 90 days in a covered shed and open shed with canvas transparete without compromising the nutritional value